Senataxin, the ortholog of a yeast RNA helicase, is mutant in ataxia-ocular apraxia 2. - Moreira, M.C. (2010)
Nat Genet. 2004 Mar;36(3):225-7. Epub 2004 Feb 8. Senataxin, the ortholog of a yeast RNA helicase, is mutant in ataxia-ocular apraxia 2. Moreira MC, Klur S, Watanabe M, Németh AH, Le Ber I, Moniz JC, Tranchant C, Aubourg P, Tazir M, Schöls L, Pandolfo M, Schulz JB, Pouget J, Calvas P, Shizuka-Ikeda M, Shoji M, Tanaka M, Izatt L, Shaw CE, M'Zahem A, Dunne E, Bomont P, Benhassine T, Bouslam N, Stevanin G, Brice A, Guimarães J, Mendonça P, Barbot C, Coutinho P, Sequeiros J, Dürr A, Warter JM, Koenig M. IGBMC (Centre National de la Recherche Scientifique, Institut National de la Santé et de la Recherche Médicale, ULP) 67404 Illkirch, C.U. de Strasbourg, France. Abstract Ataxia-ocular apraxia 2 (AOA2) was recently identified as a new autosomal recessive ataxia. We have now identified causative mutations in 15 families, which allows us to clinically define this entity by onset between 10 and 22 years, cerebellar atrophy, axonal sensorimotor neuropathy, oculomotor apraxia and elevated alpha-fetoprotein (AFP). Ten of the fifteen mutations cause premature termination of a large DEAxQ-box helicase, the human ortholog of yeast Sen1p, involved in RNA maturation and termination. PMID: 14770181 [PubMed - indexed for MEDLINE]